A first experience with digital complete overdentures - Salwa Omar Bajunaid (Saudi Dental Journal)
The development of computer-aided design/computer-aided manufacturing systems for dentistry in the 1980s resulted in the successful fabrication of crowns, fixed dental prostheses, and superstructures for both natural teeth and dental implants. Today, this technology is available for constructing digitally designed and milled, completely removable dental prostheses. The procedure uses clinical and laboratory protocols that allow fabrication of completely removable prostheses within two clinical appointments. The aim of this clinical report is to present the author’s first experience with digital complete overdentures, the practicality of this technology, and patient feedback. Compared with conventional overdentures, the fit of the digital prostheses was improved because the cameo and flanges of the prostheses were nicely shaped and rolled, and this enhanced their stability and retention. Occlusion was also excellent. However, aesthetics in terms of the alignment, shape, and size of the maxillary overdenture teeth were inacceptable. Despite some of the drawbacks identified in our study, the use of removable digital dentures does provide excellent adaptation of the denture base and requires fewer clinic visits. We anticipate that the unsatisfactory aesthetic outcomes presented in this report can be corrected with more experience. We also believe that acquiring an in-house scanning machine would be beneficial. We highly recommend including this technique in dental school curriculums at both the undergraduate and graduate levels in order to keep students and residents up to date on the latest technology available. Keywords: CAD/CAM, Digital dentures, Implant overdentures